The Role of Antimullerian Hormone in the Diagnosis of Poly Cystic Ovarian Syndrom. - Al-Taee, Hanan A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Polycystic vary syndrome (PCOS) is a common endocrine disorder, affecting up to 10% of women of reproductive age. The cardinal features of PCOS are hyperandrogenism (HA) and oligo-anovulation. Many work teams recently have relate the severity of PCOS with Anti mullerian hormone (AMH) or antral follicle count (AFC). Objective: 1) to confirm if there is an increase of serum AMH in this group of patients with PCOS, 2) to relate the AMH level to the follicle status at ultrasound (U/S) in this group, and 3) to search if AMH or AFC can serve as surrogate for the definition of PCOS. Patients and methods: Twenty five (control) and another 45 participants (with PCOS) were selected for this study. The control women had a mean age of 32.5 year (yr) and the patients group women had a mean age of 28.4 yr. Blood samples were collected from all participants, anthropometric measurements were calculated, and transvaginal U/S was performed to measure the AFC during the early follicular phase. The blood samples were assayed for AMH, follicle-stimulating hormone (FSH), Luteinizing Hormone (LH) and estradiol (E2) and total testosterone (TT).Results: Basal serum hormonal levels of LH, AMH and TT as well as AFC were significantly higher in the study group than in controls. While basal serum levels of E2 and FSH show no significant difference between the two groups. Body mass index (BMI) is significantly higher in PCOS patients. Basal serum levels of AMH  show significant positive correlation with both AFC and basal serum TT levels.The area under the receiver operating characteristic curve (ROCAUC ) for AMH and AFC show significant sensitive and specificitiesConclusion: serum AMH and AFC appear as a sensitive and specific parameter that would probably help in the diagnosis of PCOS. Both criteria need to be incorporated into the Rotterdam definition for PCOS, and it indicates PCOS only if associated with HA and/or oligo-anovulation.